Akad Penerbitan Sukuk di Pasar Modal Indonesia dalam Perspektif Fikih - Rachmawati, Eka Nuraini; ab ghani, ab mumin bin (al-'adalah, 2017)
This article discusses the concepts of contract in the perspective of Fiqh (Islamic Jurisprudence) and its implementation in Sharia Capital Market, particularly in the issuance of Corporate Sukuk and State Sukuk (SBSN). The purpose of the study is to understand the concept of akad (contract) in Islamic perspective an its implementation in sukuk issuance, mainly related to the transfer of ownership from the sukuk issuer to the investor. This study reveals that the current practice of issuance of corporate sukuk in Indonesia is only based on two models of contracts, namely Ijârah and Mudhârabah contracts. In addition, the contract structure are also varied, depending on the type of the issuer business, the purpose of funding, and the choice of contract. In the future, the issuance of corporate sukuk should have a uniformed, standardized structure, while it still comply with syariah regulation.